Susceptibility of South American pear cultivars to brown spot of pear caused by Stemphylium vesicariu - Tudela, Marisa Andrea Alumine; Gimenez, Gustavo Nestor; Di Masi, Susana Noemi; Pose, Graciela Noemí; Basanta, Mabel (Springer, 2024)
Brown spot of pear (BSP), a fungal disease, was recently detected in the Alto Valle of Río Negro region in Patagonia, Argentina. BSP is caused by Stemphylium vesicarium (teleomorph: Pleospora herbarum, syn. P. allii) in its sexual and asexual stages, and its main symptoms are lesions in fruit and leaves. The aim of the present study was to characterize the susceptibility of four main pear cultivars grown in the Alto Valle of Río Negro to infection by S. vesicarium. Over four recent growing seasons, BSP incidence and severity were monitored in an orchard with ‘Williams’, ‘Packham’s’, ‘D'Anjou’, and ‘Abate Fetel’ pear cultivars. In addition, inoculations of a pathogenic S. vesicarium strain were performed on detached fruit and leaves of the four cultivars. Both in-feld observations and in vitro inoculation experiments indicated that fruit and leaf susceptibility to BSP was markedly higher in ‘D'Anjou’ and ‘Abate Fetel’ compared to ‘Packham’s’ and ‘Williams’. These fndings provide valuable information for the correct allocation of resources to efciently monitor and control BSP.